Addition of human melanopsin renders mammalian cells photoresponsive. - Melyan, Z; Tarttelin, E; Bellingham, J; Lucas, R; Hankins, M (2005)
A small number of mammalian retinal ganglion cells act as photoreceptors for regulating certain non-image forming photoresponses. These intrinsically photosensitive retinal ganglion cells express the putative photopigment melanopsin. Ablation of the melanopsin gene renders these cells insensitive to light; however, the precise role of melanopsin in supporting cellular photosensitivity is unconfirmed. Here we show that heterologous expression of human melanopsin in a mouse paraneuronal cell line (Neuro-2a) is sufficient to render these cells photoreceptive. Under such conditions, melanopsin acts as a sensory photopigment, coupled to a native ion channel via a G-protein signalling cascade, to drive physiological light detection. The melanopsin photoresponse relies on the presence of cis-isoforms of retinaldehyde and is selectively sensitive to short-wavelength light. We also present evidence to show that melanopsin functions as a bistable pigment in this system, having an intrinsic photoisomerase regeneration function that is chromatically shifted to longer wavelengths.